Digital drone education in Sarawak: Enhancing STEM learning through hands-on training for school students - San nah sze; Piau Phang; Wei King Tiong; Kang Leng Chiew; Bui Lin Wee; Say leng goh; Sofia Akmal Abu Bakar; Richki Hardi (Penerbit Akademia Baru, 2025)
In Sarawak, concerns about low STEM enrolment, digital inclusivity gaps for rural children, and the transition from digital consumption to digital creation led to the introduction of the Drone Education Program. Participants began with foundational drone operation training, advancing to capturing images and videos. Subsequently, they were acquainted with elementary photo and video editing techniques, enabling them to enhance their drone-generated content. The aim of this research is to gauge the impact of the Drone Education Program on refining drone operations, bolstering digital editing competencies, and stimulating STEM engagement in students. In our methodology, we employed tailored pre- and post-surveys for evaluation, and younger students provided feedback via an emoji-based survey. Further analytical methods encompassed non-parametric tests, Exploratory Factor Analysis (EFA), and linear mixedeffect modelling. Results indicated significant post-intervention improvements in the targeted skills. The EFA grouped 21 Likert items into five distinct learning domains. Notable insights include district-wise variances in learning outcomes and the influential role of gender. The initiative showcases promise in confronting Sarawak's educational barriers, championing digital inclusivity, and preparing a digitally proficient generation.